MedTech Summit Berlin 2026: Where Innovation Meets Regulation - Kumar*, Arun HS (Biology, Engineering, Medicine and Science Reports, 2026)
The medical technology sector entered one of the most transformative periods in its history in 2026. Artificial intelligence had moved from experimental pilot projects into clinical reality. Software had become as critical to patient outcomes as hardware. Digital evidence was reshaping clinical evaluation, while sustainability requirements were increasingly influencing product development decisions. At the same time, regulators across Europe and around the world were working to keep pace with technologies that were evolving faster than traditional regulatory frameworks had ever been designed to accommodate. Against this backdrop, the MedTech Summit 2026, held in Berlin, Germany, from 15-18 June 2026, brought together regulators, manufacturers, notified bodies, clinicians, researchers, legal experts, and technology leaders to address the industry's most pressing challenges. The event welcomed approximately 293 attendees, including 98 speakers, and featured representation from more than 150 organisations worldwide, as well as freelancers and independent consultants.
Keywords: Editorial